Safety of Chemotherapy for Hematologic Malignancies as Regards Testicular Endocrine Function in Children and Teenagers - Grinspon, Romina (2019)
Effective treatments have increasedlife expectancy in children with hematologic malignancies, but loss offertility has become a concern. However, the effects of chemotherapy on Sertoliand Leydig cell function in boys and adolescents has received little attention.Objective: To determine whethertreatments used in boys with hematologic malignancies affect endocrine function of the developing testes.Methods: In an observational study of 97 boys (83 acute lymphocytic leukaemia, 5acute myeloid leukemia and 9 non-Hodgkin lymphoma) we assessed serum levels ofAMH and FSH and testosterone and LH as biomarkers respectively of Sertoli andLeydig cell function.Results: Sixty-one patients, with at least 1 year of follow-up after the end ofchemotherapy were included in the cross-sectional analysis. Serum AMH were within normal levels in all 37patients treated before the age of 10 years (Group A). FSH was also normal inthe vast majority, and only slightly elevated in 3. Serum levels oftestosterone and LH were within the normal levels in all of them. In the 24 patients in whom treatment ended after 10 years(Group B), AMH was also within the reference range but FSH was elevated in 8cases, suggesting a compensated primary Sertoli cell insufficiency. Similarly,testosterone levels were normal in all cases, but LH were slightly elevated in5 patients, probably indicating a compensated Leydig cell dysfunction. All 97 patients were included in the longitudinalanalysis, 58 patients completed treatment before 10 years (Group A) and 39 after10 years of age (Group B). Serum AMH was never <2 SDS in any of the patientsduring follow-up. Testosterone remained below the reference range in only onecase. In Group A, 9 patients (15.5 %) had at least one FSH value>2 SDS during follow-up. In 3 of them (7.7 %) was also >2 SDS. In GroupB, 14 patients (35.9%) had at least one FSH value >2 SDS. Eight of them(20.5 %) also had LH >2 SDS. Three (7.7 %) had only LH elevation. The proportionof patients with FSH and LH >2 SDS was higher (P=0.008 and 0.03, respectively) in Group B than in Group A. Conclusion: Therapy ofhematologic malignancies did not significantly affect Sertoli and Leydig cell functions inboys treated <10 years. Conversely, when treatment ended after pubertalonset, a compensated Sertoli and Leydig cell dysfunction was more frequentlyobserved. No risk factor could be identified in association with thecompensated endocrine dysfunction.